Factors influencing local road (JKR U2/U3) damage in Malaysia - Khalifa, Nasradeen A.; A., Zulkiple; H. F., Suhandri (Jordan University of Science and Technology, 2019)
This study configures the high loads of heavy trucks as a major source of pavement damage by causing fatigue, which leads to cracking and permanent deformation, producing rutting. Malaysia, as one of the developing countries, has a high level of road pavement damage. Through examining the cost of rehabilitating pavements, serious safety issues occur, especially when heavy trucks use local roads (JKR U2/U3), which are not designed to be used by heavy trucks. This study aims at discussing the factors influencing local road (JKR U2/U3) damage in Malaysia, from February 2013 until July 2014 at the selected area. The overall results show a positive significant interaction using WarpPLS as a tool to develop the method and SPSS is used to examine the data and generate the model. Results indicated that regression relationships between road damage and other research factors have been established with a coefficient of determination (R) of 0.71. The limitations of the study are that the observation was done according to purposive sampling technique, time was just adequate and there was no accurate measurement of truck weight. This paper highlights not only the important statistical relationship between different factors influent on local road damage, but the mechanics of truck movement on local access roads was also studied to identify relationships between truck properties and road damage and to develop an appropriate method of data collection for these local roads.